PERLINDUNGAN HUKUM BAGI KREDITUR TERHADAP JAMINAN FIDUSIA DALAM WANPRESTASI DEBITUR - Made Mulyawan Subawa (Universitas Mahendradatta, 2026)
Fiduciary is a form of guarantee for movable objects in addition to pawn which is developed by jurisprudence. Fiduciary guarantee is regulated by Law Number 42 of 1999. After the issuance of Constitutional Court Decision Number 18/PUU-XVII/2019, the executorial power of the fiduciary guarantee certificate has become different. The explanation in the ruling of the Constitutional Court Decision 18/PUU-XVII/2019 has granted the applicants' request in part and stated that the phrase contained in Article 15 Paragraph (2) and its explanation and Paragraph (3) of the Fiduciary Law is contrary to the 1945 Constitution as long as it is not interpreted as interpreted by the Panel of Judges of the Constitutional Court as contained in the Decision. The purpose of this study is to determine and describe the legal protection for creditors against Fiduciary Guarantees in the event of debtor default following the Constitutional Court Decision No. 18/PUUXVII/2019. The research method used is an empirical juridical approach, and the research specifications used in this study are descriptive analytical.